Digitalization of regional economy: concepts, problems, ways of realization - Z. D. Gasheva (Новые технологии)
The concept of digital economy has been analyzed. The concept of a regional digital economy has been formulated. The essence of the revolutionary scenario of digital market transformation has been investigated. In particular, the problems of monopolization of production and business of the regional economy, the loss of control over the economic development of the region, foreign economic intervention, seizing regional development resources have been disclosed. From the point of view of the research topic, some key terms and expressions (the ecosystem of the regional economy, functional competitiveness of economic entities, marginality of business and production, the mainstream of the regional economy) have been clarified. A SWOT analysis of the process of using digital platforms in the regional economy has been carried out.